CD8 + Tumoral as Predictor of Neoadjuvant Chemotherapy Response in Patients with Local Advanced Stage Breast Cancer - Muhammad Danar Deswangga; Yamin Alsoph (Sriwijaya Journal of Surgery, 2018)
ABSTRACT Introduction. Cancer until now has become a problem for health in the world including Indonesia. According to 2013 WHO data, cancer incidence has increased from 12.7 million cases in 2008 to 14.1 million cases in 2012. In local advanced breast cancer the treatment is neoadjuvant chemotherapy. Neoadjuvant therapy usually uses anthracycline or taxane based which can improve chemotherapy responses. Methods. This type of research is a CD8 + tumoral prognostic test used to predict neoadjuvant chemotherapy responses in patients with locally advanced breast cancer. The research was carried out in the oncology surgery clinic and inpatient Dr. Mohammad Hoesin Hospital Palembang. Assessment of CD8 + expression is done by immunohistochemistry. CD8 + expression is expressed as a percentage of cell expression, whose the cut off point is determined first. Result. There was a significant relationship between CD8 + tumoral with chemotherapy response (p = 0.033) with a sensitivity value: 43.5%; specificity: 100%, NR +: 100%; NR-: 35%; False positive: 0%; False negative: 65%; OR: 1.53. CD8 + predominantly had a good chemotherapy response in all samples of 10 (100%) patients while CD8 + non-dominant tumoral was more in a good chemotherapy response with 13 (65%) patients and poor chemotherapy response in 7 (35%) patient. Conclusion. CD8 + as a predictive factor for neoadjuvant chemotherapy responses in local advanced breast cancer has a significant relationship, with a p value = 0.033, sensitivity value: 43.5%; specificity: 100%, NR +: 100%; NR-: 35%; False positive: 0%; False negative: 65%.